2022
DOI: 10.1002/adfm.202209658
|View full text |Cite
|
Sign up to set email alerts
|

Physical Cue‐Based Strategies on Peripheral Nerve Regeneration

Abstract: Peripheral nerve injury (PNI) remains an intractable challenge in regenerative medicine. Recently, physical cue-based strategies (e.g., electrical neurostimulation, acoustic radiation, electromagnetic bioregulation, as well as directional fiber guiding, etc.) have drawn increasing attention not only as a stimulator for cell functions modulation and fate determination, but also as a morphology-index for modulating cell phenotype, proliferation, and differentiation, especially for nerve cells. More importantly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 227 publications
(247 reference statements)
0
9
0
Order By: Relevance
“…The improvement in hydrophilicity was attributed to the effective reduction of the material's surface energy with the addition of ZnO NPs and rGO. 13,20 In this study, MNGCs with microchannels made from PCL, PG, and PZG were named P-mMNGCs, PG-mMNGCs, and PZG-mMNGCs. The MNGCs without microchannels were named P-nMNGCs, PG-nMNGCs, and PZG-nMNGCs.…”
Section: Characterizations Of Mngcsmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement in hydrophilicity was attributed to the effective reduction of the material's surface energy with the addition of ZnO NPs and rGO. 13,20 In this study, MNGCs with microchannels made from PCL, PG, and PZG were named P-mMNGCs, PG-mMNGCs, and PZG-mMNGCs. The MNGCs without microchannels were named P-nMNGCs, PG-nMNGCs, and PZG-nMNGCs.…”
Section: Characterizations Of Mngcsmentioning
confidence: 99%
“…However, these methods have obvious shortcomings, such as the potential for infection, limited battery life, and low signal transmission efficiency, seriously limiting their application. 20 The self-powered strategy based on the piezoelectric effect shows great potential in providing endogenous ES as it can efficiently convert the mechanical energy generated by body movement into electrical energy continuously and stably. 21,22 (3) Growth guidance of nerve cells:…”
Section: Introductionmentioning
confidence: 99%
“…The porous structure of the electrospun fiber conduit can increase the diffusion of biomolecules and metabolic substances and effectively prevent fibrous scar deposition through pore size adjustment. More important, directional fibers can provide direct physical cues for the directional regeneration of axons from the proximal to the distal end [ 42 ].…”
Section: Fabrication Strategiesmentioning
confidence: 99%
“…Its remarkable advantage lies in the fact that injured nerves can be reconstructed in situ in a controlled and long-term sustainable manner when the cell fate/behavior and microenvironment associated with regeneration are altered. 25 Previous studies have shown that external physical stimulation can have a positive regulatory effect on the nervous system, which is not limited to the cellular level but can extend to influence nervous tissue to a certain extent. [26][27][28] Over the past few decades, physical stimulation has been clinically used as a neuro-modulation approach for both the CNS and peripheral nervous system to relieve chronic neuropathic pain and improve the neurological functions of patients with neurodegenerative diseases, e.g., Parkinson's disease (PD).…”
Section: Introductionmentioning
confidence: 99%